Flicker electroretinograms recorded with mydriasis-free RETeval system before and after cataract surgery - Miura, G (Eye (Lond), 2017)
PURPOSE: The purpose of this study is to compare the amplitudes and peak times of the flicker electroretinograms (ERGs) recorded before and after cataract surgery with the RETeval system (LKC Technologies, Gaithersburg, MD, USA) from eyes without dilation. PATIENTS AND METHODS: Thirty-two eyes of 32 patients (77.3±6.5 years) that had grade 2 Emery–Little nuclear or cortical cataract without any other abnormalities were studied. Flicker ERGs were recorded with the RETeval system under mydriatic-free conditions. Skin electrodes were used to pick-up the ERGs that were elicited by white light delivered at a rate of 28.3 Hz and intensity of 2, 8, and 32 Td-s. The amplitudes and peak times of the flicker ERGs before and after cataract surgery were compared. RESULTS: The mean amplitudes were significantly increased after the removal of the cataractous lenses at the three stimulus intensities (2 Td-s, P<0.0001; 8 Td-s, P<0.0001; and 32 Td-s, P<0.0001). The mean peak times of the flicker ERGs elicited by 2 and 8 Td-s were significantly shortened after the surgery (2 td-s, P<0.0001 and 8 td-s, P=0.0127) but not at 32 td-s (P=0.595). CONCLUSIONS: These results indicate that the presence of cataracts will affect both the amplitudes and the peak times of the flicker ERGs even if the cataract is mild. In addition, the results indicate that as stimulus intensity increases, the peak times is less affected by a cataract. The clarity of the crystalline lens should be considered when interpreting the flicker ERGs recorded with the RETeval system.